Immunotherapy Combined with Large Fractions of Radiotherapy: Stereotactic Radiosurgery for Brain Metastases—Implications for Intraoperative Radiotherapy after Resection - Herskind, Carsten; Wenz, Frederik; Giordano, Frank A. (Frontiers in Oncology, 2017)
Brain metastases (BM) represent an advanced stage cancer manifestation that affect roughly a third of all cancer patients with systemic disease. BM predominantly originate from lung, breast, or gastrointestinal cancers, and melanoma. Given the change in demographics in industrialized countries with increasing cancer frequencies but also improved diagnostics and more long-term survivors, the incidence is believed to rise further. Depending on the clinical condition, treatment options for BM include surgery, whole-brain radiotherapy or stereotactic radiosurgery (SRS) while chemotherapy has only limited activity. There is accumulating evidence that high single doses of ionizing radiation can be highly efficient in eliciting a broad spectrum of local, regional and systemic tumor-directed immune reactions. This newly discovered ability has been uncovered especially in combination with immune checkpoint blockade with which it appears to synergize. We here review the current notion of immune responses to high single doses and specifically discuss if IORT may be suitable as immunizing event when treating beyond the surgical cavity in brain metastases.